Democracy and Good Governance in Nigeria: The Imperatives of Supporting Institutions - Ntuk, Udeh Godwin (Asian Development Policy Review, 2017)
Democracy thrives better where good governance is the rule not exception. Since Nigeria returned to democratic rule in 1999, the people expects more from the state. This research was conducted to appraise the role of key pillars of democracy and good governance in Nigeria. These include but not limited to political party, INEC, Judiciary and the Public Service. It was found out in this research that there is selective compliance with court pronouncements by the executive. Party primaries was seen as the litmus test for credible elections in Nigeria. INEC, PDP and former President Goodluck Jonathan were commended for conducting credible polls and relinquishing power freely. The study concluded that success of democracy in Nigeria is contingent on strong democratic institutions. It was recommended that politicians must eschew traditional greedy material accumulation which impedes democratic deliverables. An independent judiciary was urged to rise to the occasion by delivering justice to all- persons and institutions brought before it.